Team creativity versus team learning: transcending conceptual boundaries to inspire future framework building. Issue 1 (1st January 2016) - Boon, Anne; Vangrieken, Katrien; Dochy, Filip
Abstract : The purpose of this study was to compare team creativity and team learning – approached as interpersonal processes – conceptually and empirically and thereby inspire future framework building on team creativity. First, both concepts were compared based on present literature. In the next – empirical – step, a questionnaire consisting of a range of team creative and learning processes was developed and validated among 112 design teams, encompassing 540 employees. By means of a questionnaire validation protocol, this study assessed the empirical similarities and interrelation between team creative and learning processes. Several conceptual similarities in both frameworks were identified. The theoretically expected difference between team creativity and team learning (i.e. the aspect newness) was not supported by our empirical results. A five-factor model – consisting of team creative efficacy, facilitating team processes, basic team processes, error communication, and co-construction was validated. This study contributes to the present literature by showing that future theorising on team creative processes can certainly draw inspiration from the team learning literature in several ways.